2013
DOI: 10.1021/es4024089
|View full text |Cite
|
Sign up to set email alerts
|

Copper Redox Transformation and Complexation by Reduced and Oxidized Soil Humic Acid. 1. X-ray Absorption Spectroscopy Study

Abstract: Natural organic matter (NOM) exerts strong influence on copper speciation and bioavailability in soils and aquatic systems. In redox-dynamic environments, electron transfer reactions between copper and redox-active moieties of NOM may trigger Cu(I) and Cu(0) formation. To date, little is known about Cu-NOM redox interactions and Cu(I) binding to NOM. Here, we present X-ray absorption spectroscopy results on copper redox transformations upon addition of Cu(II) or Cu(I) to untreated and electrochemically reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 68 publications
4
79
1
Order By: Relevance
“…This may be due to the decreasing Cu solubility with increasing pH, as generally observed in acidic soils under reducing conditions. Moreover, recent studies by Biasioli et al, 12 Fulda et al 37 and Matocha et al 38 have shown that, under anoxic conditions, Cu(II) can be reduced to Cu(I) or Cu(0) and subsequently stabilized as insoluble Cu(I)-humic acids complexes or precipitated as Cu2O. Huang et al 18 presented similar results for OM-amended paddy soils.…”
Section: Column Experimentsmentioning
confidence: 79%
“…This may be due to the decreasing Cu solubility with increasing pH, as generally observed in acidic soils under reducing conditions. Moreover, recent studies by Biasioli et al, 12 Fulda et al 37 and Matocha et al 38 have shown that, under anoxic conditions, Cu(II) can be reduced to Cu(I) or Cu(0) and subsequently stabilized as insoluble Cu(I)-humic acids complexes or precipitated as Cu2O. Huang et al 18 presented similar results for OM-amended paddy soils.…”
Section: Column Experimentsmentioning
confidence: 79%
“…As XANES signals are highly sensitive to the elemental oxidation state (Fulda et al, 2013b), LCF analysis of the normalized XANES spectra was conducted for Ce speciation. Athena software was used to perform LCF analysis of reference spectra as described by Levard et al (2012).…”
Section: Reliability Analysis Of Xafs Measurementmentioning
confidence: 99%
“…More recently, X-ray absorption near edge structure (XANES) and extended X-ray absorption fine-structure (EXAFS) assay, followed by liner combination fitting (LCF), were used to study the transformation of metals in complex environmental/biological matrix in a quantitative way (Fulda et al, 2013a(Fulda et al, , 2013b. These methods might also be suitable for the quantification of NPs dissolution in complex matrix without pre-separating the ions and particles.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that Cu isotope fractionation could be induced by various low temperature processes, such as adsorption, mineral dissolution, redox reaction, complexation with minerals and/or organic matters, and biotic incorporation [38,39,40,41,42,43,44,45,46,47]. In these processes, the isotopic fractionation (expressed as Δ 65 Cu P-I ) was determined for describing the enrichment or depletion of Cu isotope ( 63 Cu or 65 Cu) in the product compared to the initial materials, and was calculated as following: Δ 65 Cu P-I = δ 65 Cu P − δ 65 Cu I where δ 65 Cu p and δ 65 Cu I were the isotope ratio in the product P and initial material I, respectively.…”
Section: Cu Isotopic Fractionation During Low Temperature Processementioning
confidence: 99%